2009
DOI: 10.1038/ismej.2009.75
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community gene expression within colonies of the diazotroph, Trichodesmium, from the Southwest Pacific Ocean

Abstract: Trichodesmium are responsible for a large fraction of open ocean nitrogen fixation, and are often found in complex consortia of other microorganisms, including viruses, prokaryotes, microbial eukaryotes and metazoa. We applied a community gene expression (metatranscriptomic) approach to study the patterns of microbial gene utilization within colonies of Trichodesmium collected during a bloom in the Southwest Pacific Ocean in April 2007. The survey generated 5711-day and 5385-night putative mRNA reads. The majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 67 publications
8
98
0
Order By: Relevance
“…Heterotrophic bacteria were recently shown to have an active role in gene transcription as epibionts within the Trichodesmium consortia and are suggested to alter the Trichodesmium metabolism (Hewson et al, 2009b). Our experimental observations represent a contrasting 'best case scenario', whereby algal bloom, crash and subsequent vertical flux were largely isolated from these aforementioned microbial transformation processes and, consequently, provide an upper limit of potential vertical C and N fluxes following Trichodesmium bloom crashes.…”
Section: Abrupt and Synchronized Bloom Demisementioning
confidence: 80%
See 1 more Smart Citation
“…Heterotrophic bacteria were recently shown to have an active role in gene transcription as epibionts within the Trichodesmium consortia and are suggested to alter the Trichodesmium metabolism (Hewson et al, 2009b). Our experimental observations represent a contrasting 'best case scenario', whereby algal bloom, crash and subsequent vertical flux were largely isolated from these aforementioned microbial transformation processes and, consequently, provide an upper limit of potential vertical C and N fluxes following Trichodesmium bloom crashes.…”
Section: Abrupt and Synchronized Bloom Demisementioning
confidence: 80%
“…One intriguing aspect of this PCD response is the potential role that quorum sensing (QS) may have in triggering its onset. QS is known to regulate the cell-cell communication and population response through the activation of different metabolic pathways including cell death (Dandekar et al, 2012), and QS has been recently documented to control phosphorus acquisition among Trichodesmium-epibiont consortia (Hewson et al, 2009b;Hmelo et al, 2012). Further investigation is needed to identify whether QS has any role in the PCD of Trichodesmium.…”
Section: Abrupt and Synchronized Bloom Demisementioning
confidence: 99%
“…Thus, most highly expressed genes were shared by multiple taxa, although the SAR11 members HTCC1002, HTCC1062 and HIMB114 as well as MS024-2A and N. maritimus SCM1 did not have as strong a pattern as the others (Supplementary Figure S3). Previous observations from marine metatranscriptomic data (Hewson et al, 2009;Stewart et al, 2011) support this conclusion, and suggest that an analysis restricted to only the more highly expressed genes is likely to miss unique functional capabilities that distinguish taxa.…”
Section: Transcriptome Characteristicsmentioning
confidence: 86%
“…One explanation is that very few grazers are thought to prey on Trichodesmium spp. (Hawser et al, 1992;Roman, 1992, 1994); therefore, these large filamentous colonies offer protective habitat in the open ocean, and they are known to harbor a community of heterotrophic bacteria and other filamentous cyanobacteria (Paerl and Bebout, 1989;Siddiqui et al, 1992;Sheridan et al, 2002;Hewson et al, 2009). Measurements of diurnal nitrogen fixation have shown that Trichodesmium nitrogen-fixation rates drop to below detection level at the start of the dark cycle (e.g., Capone et al, 2005;Staal et al, 2007).…”
Section: Discussionmentioning
confidence: 99%